The influence of urban public park as a restorative environment affecting mental well-being among community in Kuala Lumpur / Nur Adlin Irdina Hamzah and Farid Al Hakeem Yuserrie - Hamzah, Nur Adlin Irdina; Yuserrie, Farid Al Hakeem (2023)
Urban growth creates challenges recognized by the global community. Many studies in the related field have drawn a connection that natural and green places are more likely to be restorative to a person's health, especially when compared to those living in cities. This study aimed to investigate the effect of urban public parks as a restorative environment affecting mental well-being as perceived by urban dwellers specifically in Kuala Lumpur. A qualitative approach was acquired through multiple sources, including document reviews, image-based interviews, and field observations. This study uses the PERMA framework to study the attributes of urban public parks to achieve good mental well-being. Hence, the instrument will then be used to measure the level of mental well-being of urban dwellers by analysing an existing urban public park as a case study. In brief, data from findings confirm the presence of restorative elements can be perceived by users and it is claimed to be crucial for an increasingly urbanized society's quality of life as a location to recover oneself. Therefore, current designers and landscape architects are recommended to add more special features that can make the park have novel elements by implementing the theory of restorative environment and its qualities when designing or optimizing parks.